KONFLIK PANDAWA-KURAWA DALAM PANDANGAN KARL MARX - Mardjono Mardjono (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2010)
In puppet show, there is a war of life and death between Pandawa and Kurawa called Baratayuda Jayabinangun. Object of this research is focussed on the characters Pandawa and Kurawa. They represent evil and virtue, protagonist and antagonist, truth versus evil. This reseacrh aims to describe  the aspects of  Marx theory of conflict in relation to Baratayuda as the conflict solution of Kurawa and Pandawa. The researcher uses sociological perspective by positioning the Marx theory of conflict as the analysis  tools. The result shows that: (1) the conflict of Kurawa-Pandawa is based on the material as well as psichological factors, namely kamukten of the state Ngamarta and Ngastina and Duryudana’s characteristic, ambeg angkara murka; (2) the conflict of Kurawa-Pandawa can be categorized as social conflict; (3) Pandawa’s struggle cannot be categorized as the struggle between  the poor and the rich to avoid Kurawa’s pressure. It is not proporsional to be placed in Baratayuda context for the conflict of Kurawa-Pandawa is not formed of economic factor.Key words: Bharatayuda, conflict, Pandawa-Kurawa, Marx